The Relationship between Students’ Motivation, Self-Efficacy, and Their Writing Achievement - Sakinah, Rina; Dewi, Ratna; Nappu, Syamsiarna (Institut Agama Islam Negeri Palopo, 2025)
This study aimed to analyze the relationship between students’ motivation in writing, self-efficacy and their writing achievement. The variables of this study were: Writing Achievement as the dependent variable (Y) and Motivation In Writing as the first independent variable (X1) and Self-Efficacy as the second independent variable (X2). The population of this study were 252 students in tenth grade of SMA Negeri 5 Takalar while the sample of this study amounted to 35 students in the tenth grade of SMA Negeri 5 Takalar. Data collection was carried out by using questionnaire and test. Data analysis was carried out by using pearson correlation test. The results of this study showed that the average score of students’ motivation in writing was 73.72, Self-Efficacy score was 73.00 and Writing Score was 51.00. As for the pearson correlation test, the significance of motivation in writing was 0.229, which means the first independent variable (X1) motivation in writing has a low correlation on dependent variable (Y) writing score and the significance of self-efficacy was 0.382, which mean the second independent variable (X2) self-efficacy has low correlation on dependent variable (Y) writing score. It can be concluded that the students’ in SMA Negeri 5 Takalar has high motivation in writing, medium in self-efficacy and fair in writing. Furthermore, the relationship between students’ motivation in writing, self-efficacy towards students’ writing achievement is low.